Retrospective Study of Adverse Events of Chemotherapy in Cats - Cunha, Simone Carvalho dos Santos; Silva, Franciele Basso; Corgozinho, Katia Barão; Silva, Kássia Valéria Gomes Coelho da; Ferreira, Ana Maria Reis (Acta Scientiae Veterinariae, 2018)
Background: Clients who seek veterinary care for pets with cancer are often concerned about the potential negative impact of chemotherapeutic treatments on their animals’ quality of life. A consensus currently exists in veterinary oncology regarding the quantification and rating of adverse treatment effects in dogs and cats in response to chemotherapy agents. This grading system is referred to as Veterinary Cooperative Oncology Group - Common Terminology Criteria for Adverse Events. The purpose of this retrospective case series was to investigate the delayed acute effects of chemotherapy drugs in cats receiving cancer treatment. Materials, Methods & Results: Medical records were reviewed to determine the chemotherapy agent used and delayed adverse effects. Side effects were classified according to Veterinary Co-operative Oncology Group grading. All cats were evaluated after the first chemotherapy administration, after a single dose. The reported effects included hematologic effects (e.g., neutropenia, thrombocytopenia, increases in liver enzymes, and azotemia), gastrointestinal effects (e.g., vomiting, diarrhea, and inappetence), and sepsis. All of the cats in this study received ondansetron and omeprazol in the first five days following chemotherapy administration. If vomiting occurred with oral medication, maropitant was administered subcutaneously for three consecutive days. If diarrhea (> grade II) occurred, probiotics were administered for seven days. Hematologic examination was performed 3-14 days after chemotherapy. If neutropenia (> grade III) occurred, Human granulocyte colony stimulating factor was administered subcutaneously for three consecutive days together with prophylactic antibiotics. Lomustine, carboplatin, vincristine, doxorubicin, cyclophosphamide, mitoxantrone, and vinblastine were administered in 33%, 19%, 16%, 5%, 16%, 10% and 2% of the cases examined, respectively. The most common adverse events were vomiting, inappetence, neutropenia, and thrombocytopenia. Vomiting occurred in 6% cases, most of them associated with cyclophosphamide. Inappetence/anorexia affected 12% of the cases, mostly those involving cyclophosphamide or doxorubicin. Neutropenia was observed in 22% of the cases, with cyclophosphamide, followed by carboplatin and lomustine. According to the current grading system of adverse effects induced by chemotherapy, grade I toxicity was observed in 83% of the cases, whiles grade II-IV were observed in 7%, 8%, and 2% of the cases examined, respectively. Discussion: In general, the chemotherapy regimens in the cases examined were well tolerated. The toxicity experienced was infrequent and mostly mild, thereby resulting in satisfactory tolerability of the chemotherapy regimens. According to the current grading system for the adverse effects of chemotherapy, 83% of the cases examined included grade I, indicating that most of the cats experienced asymptomatic, or mild symptoms, and medical intervention was not needed. In previous studies of dogs and cats, a severe adverse event following chemotherapy was reported for fewer than 1 in 4 animals, and approximately 3-5% experienced a serious adverse event that led to hospitalization. In the present study, 2% of the cats experienced serious or life threatening adverse events. The only chemotherapeutic agent that was associated with inappetence, vomiting, and neutropenia was cyclophosphamide. Based on the data examined, we would recommend that cyclophosphamide should be used with caution for the treatment of cancer in cats, with adequate antiemetic and nutritional support available if needed. In addition, febrile neutropenia/sepsis may be avoided by using a fractionated schedule.